Youth Activism and Digital Advocacy: Indonesian Young Generation's Solidarity with Palestine - Andriansyah, Yuli (Millah: Journal of Religious Studies, 2025)
The transformation of Palestinian solidarity movements through digital platforms represents a critical development in contemporary youth activism, particularly within Muslim-majority contexts where religious identity intersects with political engagement. This editorial examines how Indonesian youth organizations have leveraged digital technologies to mobilize support for Palestine during the 2024-2025 period, building upon historical foundations established since the Soekarno era. The analysis synthesizes recent scholarship on digital activism, crowdfunding initiatives, social media campaigns, and youth mobilization strategies, drawing from empirical studies of hashtag movements, philanthropic organizations, and student networks across Indonesia. Indonesian youth have demonstrated remarkable sophistication in utilizing platforms for solidarity expression, developing diverse campaigns including humanitarian crowdfunding that capitalizes on cultural inclinations toward charitable giving, hashtag activism that functions as tools for mobilization and identity formation, and boycott movements legitimized through religious authority. Islamic university student organizations play multifaceted roles serving as vehicles for political consciousness formation and transnational coordination, while innovative collaborations such as K-pop fandom networks construct digital solidarity through Islamic-pop aesthetics. These movements face significant challenges including maintaining sustained engagement within attention economies, navigating platform governance and algorithmic gatekeeping, and translating online activism into structural change. However, opportunities exist through building institutional capacity, developing interfaith coalitions that transcend religious boundaries, and creating educational partnerships supporting Palestinian resilience. The sustainability of youth-led digital activism depends on integrating online advocacy with community-based initiatives, navigating ideological tensions within collaborative frameworks, and developing mechanisms that extend beyond crisis response toward long-term solidarity infrastructure supporting Palestinian institutions and communities.